Rifampicin-Loaded Mesoporous Silica Nanoparticles for the Treatment of Intracellular Infections - Santhni Subramaniam; Nicky Thomas; Hanna Gustafsson; Manasi Jambhrunkar; Stephen P. Kidd; Clive A. Prestidge (MDPI AG, 2019)
Infectious diseases remain a major burden in today’s world, causing high mortality rates and significant economic losses, with >9 million deaths per year predicted by 2030. Invasion of host cells by intracellular bacteria poses treatment challenges due to the poor permeation of antimicrobials into the infected cells. To overcome these limitations, mesoporous silica nanoparticles (MSNP) loaded with the antibiotic rifampicin were investigated as a nanocarrier system for the treatment of intracellular bacterial infection with specific interest in the influence of particle size on treatment efficiency. An intracellular infection model was established using small colony variants (SCV) of S. aureus in macrophages to systemically evaluate the efficacy of rifampicin-loaded MSNP against the pathogen as compared to a rifampicin solution. As hypothesized, the superior uptake of MSNP by macrophages resulted in an enhanced treatment efficacy of the encapsulated rifampicin as compared to free antibiotic. This study provides a potential platform to improve the performance of currently available antibiotics against intracellular infections.